Effectiveness of Archive Management at the Food Security Office of South Sulawesi Province (Pinisi Journal of Officers Review, 2024)
Archive management is very much needed in an organization because by organizing archives properly information services in an agency can run smoothly, archives are the center of memory in an agency, if when employees need or need data or information, it will be found in the archives, because archives are a storage place for evidence of the results of activities or transactions carried out during activities. This study focuses on knowing how effective archive management is at the Food Security Office of South Sulawesi Province. Therefore, research has significant in identifying archival governance that affects effectiveness in archives. This research is qualitative, therefore to achieve the research objectives used All indicators used in this study are considered less effective based on the results of the study. Data collection methods used include documentation, interviews, and observation. The indicator in question is that the storage and arrangement of archives is less effective because it does not follow the standard operating procedures set in the office. Archive security is effective because it has stored archives properly. Archive maintenance is less effective because the archive storage area cannot be categorized as feasible. Prevention of archive damage is less effective because the archive storage room is not maintained. The archive depreciation system cannot be categorized because the archive depreciation system has never been implemented. This study presents new information by linking detailed theories and research loci different from previous research on the effectiveness of archive governance so that it can be used as evaluation material for research loci to increase effectiveness in archives.